Karaoke upgrade module - Yeo, Eileen Lee Ching. (2008)
The full product development process of a Karaoke Upgrade Module is recorded from concept development to prototype stage. The module is developed to upgrade a non-karaoke video compact disc player to perform karaoke with scoring functions when it is connected between the player and a television through audio and video connections.